Role of Doppler Saline Sonosalpingography in Evaluation of Tubal Factors in Women with Infertility: A Cross-sectional Study - Sonal Sangwan; Bindu Bajaj; Sheea Marwah; Asmita Saran; Ayushi Jainth (Journal of Clinical and Diagnostic Research)
Introduction: The contribution of tubal factors to infertility is up to 30%. One of the tests used to evaluate tubal factor infertility is Doppler saline Sonosalpingography (SSG). The basic principle of SSG is to distend the uterine cavity with isotonic saline, which helps identify the uterine contour, intrauterine pathology, endometrial thickness and the presence of fluid in the Pouch of Douglas (POD). Adding Doppler increases its efficiency and accuracy. Aim: To ascertain the role of Doppler saline SSG in tubal infertility. Materials and Methods: This cross-sectional study was done for 18 months in the Obstetrics and Gynaecology Department of Vardhman Mahavir Medical College and Safdarjung Hospital, New Delhi, India involving 200 women with either primary or secondary infertility. These women were recruited in the mid-follicular phase after obtaining written informed consent. Patients underwent Doppler SSG to assess tubal patency and the findings were compared with Diagnostic Hysterolaparoscopy (DHL). Diagnostic tests were used to calculate sensitivity, specificity, Positive Predictive Value (PPV) and Negative Predictive Value (NPV). Inter-rater kappa agreement was used to find out the strength of the association between Doppler Saline SSG and diagnostic laparoscopy. A p-value of less than 0.05 was considered significant. The data was entered into an MS Excel spreadsheet and analysis was done using the licensed version of Statistical Package for Social Sciences (SPSS) version 21.0. Results: The mean age and mean duration of infertility were reported to be 29 years and five years, respectively. The sensitivity of Doppler SSG for tubal patency was reported as 85.4%, the specificity as 95.8%, PPV as 95.3%, NPV as 86.8% and the accuracy for tubal patency was 90.6%. Doppler SSG and laparoscopic chromopertubation findings had substantial association (k value -0.62). Conclusion: Doppler SSG is a reliable method for the assessment of tubal factors and can be used as a screening modality with high sensitivity and specificity.